Pendampingan Masyarakat Sekitar Kawasan Hutan Produksi Kotawaringin Kabupaten Bangka - Ari Agung Nugroho; Wenni Anggita; Nanang Wahyudin (Universita Bangka Belitung, 2022)
Forest implementation as a national developmentasset is very beneficial for life and livelihood. Participation in thelevel of community involvement in the empowerment processaround the Kotawaringin forest area, Bangka Regency, BangkaBelitung Islands Province, as well as an effective communityempowerment strategy or in accordance with the socio-culturalconditions of the community around the forest area have thepotential to improve community welfare and forest sustainability.Empowering local communities aims to determine theimplementation of effective community empowerment models andstrategies for communities living around forest areas inaccordance with local conditions and potential. The communityempowerment method used is the formulation of effectivecommunity empowerment models and strategies for communitiesaround forest areas by planting hybrid coconuts that are inaccordance with local conditions and potential. Various stageswere carried out in empowering the community in the first forestarea, in the form of raising awareness by providing understandingto the community through socialization activities regarding themanagement of production forest areas. The next stage ofplanning is by involving the community in compiling activityprograms for production forest groups, community participationbecomes a learning medium for the community in compiling anactivity program. The results of this empowerment activity areseen from an economic perspective, namely that the communitycan improve the family economy by utilizing forest areas asbusiness products and utilizing production forest areas. Whenviewed from an educational perspective, it is in the form ofincreasing the capacity of human resources, community welfarein maintaining and preserving forest areas. And when viewedfrom a social perspective, namely the creation of cooperation andmutual cooperation between village communities in maintainingand utilizing production forest areas. The expected output incommunity empowerment will be input for communityempowerment around production forests in Kotawaringin, BangkaRegency.